Membrane Particles Derived From Adipose Tissue Mesenchymal Stromal Cells Improve Endothelial Cell Barrier Integrity - Merino, Ana; Sablik, Marta; Korevaar, Sander S.; López-Iglesias, Carmen; Ortiz-Virumbrales, Maitane; Baan, Carla C.; Lombardo, Eleuterio; Hoogduijn, Martin J. (Frontiers in Immunology, 2021)
Proinflammatory stimuli lead to endothelial injury, which results in pathologies such as cardiovascular diseases, autoimmune diseases, and contributes to alloimmune responses after organ transplantation. Both mesenchymal stromal cells (MSC) and the extracellular vesicles (EV) released by them are widely studied as regenerative therapy for the endothelium. However, for therapeutic application, the manipulation of living MSC and large-scale production of EV are major challenges. Membrane particles (MP) generated from MSC may be an alternative to the use of whole MSC or EV. MP are nanovesicles artificially generated from the membranes of MSC and possess some of the therapeutic properties of MSC. In the present study we investigated whether MP conserve the beneficial MSC effects on endothelial cell repair processes under inflammatory conditions. MP were generated by hypotonic shock and extrusion of MSC membranes. The average size of MP was 120 nm, and they showed a spherical shape. The effects of two ratios of MP (50,000; 100,000 MP per target cell) on human umbilical vein endothelial cells (HUVEC) were tested in a model of inflammation induced by TNFα. Confocal microscopy and flow cytometry showed that within 24 hours >90% of HUVEC had taken up MP. Moreover, MP ended up in the lysosomes of the HUVEC. In a co-culture system of monocytes and TNFα activated HUVEC, MP did not affect monocyte adherence to HUVEC, but reduced the transmigration of monocytes across the endothelial layer from 138 ± 61 monocytes per microscopic field in TNFα activated HUVEC to 61 ± 45 monocytes. TNFα stimulation induced a 2-fold increase in the permeability of the HUVEC monolayer measured by the translocation of FITC-dextran to the lower compartment of a transwell system. At a dose of 1:100,000 MP significantly decreased endothelial permeability (1.5-fold) respect to TNFα Stimulated HUVEC. Finally, MP enhanced the angiogenic potential of HUVEC in an in vitro Matrigel assay by stimulating the formation of angiogenic structures, such as percentage of covered area, total tube length, total branching points, total loops. In conclusion, MP show regenerative effects on endothelial cells, opening a new avenue for treatment of vascular diseases where inflammatory processes damage the endothelium.